Quality of life of people living with HIV/AIDS before and after receiving antiretroviral therapy - Kariwala, Peeyush; Kandpal, Sunil Dutt; Singh, Arvind Kumar; Pathak, Anurag; Dixit, Sumeet (Indian Journal of Community Health, 2022)
Background- HIV/AIDS is a chronic illness. Besides having serious morbidities, opportunistic infections, it also adversely affects quality of life of People Living with HIV/AIDS (QOL- PLHIV). Early and prompt initiation of antiretroviral therapy (ART) might improve quality of life of PLHIV in various domains like psychological, physical, environment level of independence, social relationship and spirituality/religion/personal beliefs. Material and methods- The study was conducted at a medical institute of North India. Patients attending ART centre of the institute for the treatment of HIV/AIDS were interviewed on WHOQOL-HIV questionnaire. Aim and objectives- To assess and compare quality of life of people living with HIV/AIDS at initiation and after 6 months of receiving antiretroviral therapy. Result- QOL-PLHIV was improved in various domains when assessed after six months of receiving ART. For physical domain mean score increased from 12.83 to 13.85, for psychological domain from 12.54 to 14.31, for level of independence from 12.95 to 13.21, for social relationship from 12.46 to 14.15, for environment domain from 11.98 to 13.15 and for spirituality/religion/personal belief mean score increased from 11.41 to 11.96. Respective standard deviation was decreased when compared from before initiation of ART to six months after receiving ART. Conclusion – Quality of life of people living with HIV/AIDS was improved significantly after receiving ART.